Retrospective Single-Centre Descriptive Study of Characteristic and Management of Paediatric vs Adult Patients Presenting with Craniomaxillofacial Fracture - Tania, Vika; Handayani, Siti; Santoso, Imam; Rodjani, Ines Hadianesti (Lingkar Studi Bedah Plastik Foundation, 2024)
Introduction: Pediatric facial fractures are recognized as separate entities from those occurring in the adult. They differ significantly in their epidemiology, diagnosis and treatment. An understanding of the cause, severity, and distribution of maxillofacial and skull vault trauma and associated injuries can assist in establishing clinical and research priorities for prevention and effective treatment of these injuries. Because there were no studies of maxillofacial injuries in a large series in Cipto Mangunkusumo Hospital, we retrospectively analyzed the characteristics of facial injury treated at our hospital from January 2009 to December 2013. Method: This research is a descriptive study to calculate and compare pediatric and adult maxillofacial fractures between 2009 until 2013. Total sampling of all medical record of maxillofacial trauma patient who came to Cipto Mangunkusumo Hospital form January 2009 until December 2013 was recorded. All data including age, gender, distribution of fracture site, etiology of fracture and fracture treatment were noted. Severity of mandibular and midface fracture also recorded along with their specific fracture distribution. Results: We recorded 409 patients with craniomaxilofacial (CMF) injuries for 5 previous years that being treated in Cipto Mangunkusumo Hospital. 17.6%(72) of these patients were pediatrics patient with age younger than 18 years old. From the gender distribution we can see that most of the patient were male (85.3%) with motorcycle as the main cause of trauma (75.6%). We can also see that midface fractures was highly suffered not only in adult patient but also in the pediatrics (58.7%) with orbital, nasal and zygomatic complex fractures as the top three most common fracture site. As for isolated mandible fractures share 22.7% from total fractures, and 18.6% suffered from both midface and mandible fracture. From all of these trauma patients, only 42.3% underwent open reduction and internal fixation surgery, while 28.9% refuse treatment. Conclusion: Maxillofacial trauma is not common in children; however, the incidence is increasing in this country. Although the principles of treatment follow as the adult’s, a few special considerations have to be taken into account in order to improve quality of life of the child in both short and long term. A multidisciplinary approach in the management is therefore highly recommended. Preventive measures and treatment plans in children and adult should be designed while keeping in mind their difference.